Investigative research theory and practice - Layder, Derek (SAGE Publications, Inc., 2018)
With its unique modelling and mapping of social processes, investigative research offers an alternative approach to social research. This book guides you through the theoretical grounding and rules you need to effectively combine the evidence-based explanations of social behaviour and distinctive strategies of data collection associated with investigative research.